PENGARUH MOTIVASI DAN KOMITMEN DALAM MENINGKATKAN KINERJA PEGAWAI PADA KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BULUKUMBA - Andi Isna Khumaerah; Romansyah Sahabuddin; Uhud Darmawan Natsir (Cross-border, 2022)
This study aims to determine the effect of motivation and commitment on employee performance. The sample in this study was 50 respondents. Data collection techniques are carried out by means of observation, questionnaires, and documentation. The data analysis technique consisted of validity test, reability test, classical assumption test consisting of normality test, multicollinearity test, and heteroscedasticity tes, multiple regression analysis test, descriptive analysis test, and hypothesis testing. The results of the study show that motivation and commitment have a positive and significant impact on employee performance at the Bulukumba Regency Population and Civil Registration Office. Based on the results of 14.723 this value is greater than the table which is 3.19 or 14.723 > 3,19.